The expression of Ki-67 and Glypican -3 in hepatocellular carcinoma was evaluated by comparing DWI and 18F-FDG PET/CT - Wang, Xuedong; Li, Lei; Wang, Linjie; Chen, Min (Frontiers in Oncology, 2023)
Objective: The value of DWI and 18 F-FDG PET/CT in evaluating the expression of Ki-67 and GPC-3 in hepatocellular carcinoma (HCC ) was compared.Materials and methods: Ninety-four patients with primary HCC confirmed by pathology were retrospectively divided into high-and low-Ki-67-expression and positive-and negative-Glypican (GPC)-3 groups. The ADC and SUVmax values of the lesions in both groups were measured. Receiver operating characteristic (ROC) curves were used to evaluate the identification efficiency of parameters with significant differences for each group of lesions, and the area under the curve (AUC) was calculated. The combined ADC and SUVmax values were analyzed by binary logistic regression. The Delong test was used to compare the AUC values of the combined and single parameters. Pearson (in line with normal distribution) or Spearman (in line with abnormal distribution) correlation analysis was used to analyze the correlation.The ADC value of the high-Ki-67-expression group was lower than that of the low-Ki-67-expression group (P<0.05), and the SUVmax value of the high-expression group was higher than that of the low-expression group (P<0.05). The ADC value of the positive-GPC-3 group was lower than that of the negative group (P<0.05), and the SUVmax value of the positive group was higher than that of the nega.tive group (P< 0.05). The combined ADC and SUVmax values in the GPC-3 group were better than those of a single parameter (P<0.05). There was a strong negative correlation between the SUVmax value and ADC value in the Ki-67 group (R=-0.578, P<0.001) and a weak negative correlation between the SUVmax value and ADC value in the GPC-3 group (R=-0.279, P=0.006). The SUVmax value was strongly positively correlated with the Ki-67 expression index (R=0.733, P<0.001), while the ADC value was strongly negatively correlated with the Ki-67 expression index (R=-0.687, P<0.001).Conclusion: DWI and 18 F-FDG PET/CT can be used to evaluate the expression of Ki-67 and GPC-3 in HCC, and there is a certain orrelation between the ADC value and SUVmax. Combined DWI and 18 F-FDG PET/CT is superior to a single technique in evaluating the expression of GPC-3 in HCC patients. However, the combined model did not benefit the Ki-67 group..